Mathematical Models for Predicting Electric Vehicle (EV) Charging Demand in Urban Areas - Tiara Shella; Aura Sabila (International Journal of Electrical Engineering, Mathematics and Computer Science, 2024)
As electric vehicles (EVs) gain popularity, understanding the demand for EV charging infrastructure becomes essential for effective urban planning. This paper develops mathematical models to predict EV charging demand based on various factors, including population density, traffic patterns, and energy consumption data. The models provide valuable insights for city planners regarding the optimal placement and capacity of EV charging stations to meet future demand, facilitating the transition to a more sustainable urban environment.